Effects of AM3 (Inmunoferon®) on increased serum concentrations of interleukin-6 and tumour necrosis factor receptors I and II in cyclists - Cordova, A.; Monserrat, J.; Villa, G.; Reyes, E.; Alvarez-Mon Soto, M. (Journal of Sports Sciences, 2006)
The aims of this study were to examine the changes in plasma concentrations of inflammatory cytokines induced by training and competition in professional cyclists. We report the serum concentrations of interleukin-6 (IL-6), tumour necrosis factor alpha (TNF-a), tumour necrosis factor receptors I and II (TNFR-I and -II) in a prospective, randomized, double-blind trial involving the administration of AM3 (Inmunoferon®), an oral booster immunomodulator, or placebo to 16 professional cyclists (n=8 in each group) for 65 consecutive days. Serum was collected just before treatment began (baseline), at the end of pre-competition training, before the mountain stage of the competition (60 days), 4 h after finishing this stage (62 days), and 18 h after the fifth and last day of competition (65 days). To determine the normal levels of cytokines and soluble TNF receptors, individual samples from 14 moderately trained healthy controls were studied. After 60 days of training, the serum concentrations of IL-6 did not differ significantly from those at the beginning of the study for either group of cyclists (placebo and AM3). A significant rise was seen in IL-6 concentrations in both the AM3 and placebo groups at 62 days, 4 h after finishing the mountain stage. The increase was significantly greater in the placebo group than in the AM3 group. At 65 days of treatment, 18 h after the fifth and last day of competition, IL-6 concentrations were similar to those recorded at the end of the training, but were significantly higher in the placebo group than in the AM3 group. At the end of training, serum TNFR-I concentrations in both groups of cyclists were significantly lower than at baseline. The concentrations of serum TNFR-I and -II both 4 h after finishing the mountain stage and 18 h after the fifth and last day of competition were significantly higher than those recorded after training in both groups. Professional cycling competition is associated with increases in serum IL-6 and TNFR-I and -II concentrations. Inmunoferon treatment reduced significantly the concentrations of IL-6 but not those of TNFR-I and -II.